2013
DOI: 10.1038/ni.2789
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signatures of antibody responses derived from a systems biology study of five human vaccines

Abstract: Many vaccines induce protective immunity via antibodies. Recent studies have used systems biological approaches to determine signatures that predict vaccine immunity in humans, but whether there is a ‘universal signature’ that can predict antibody responses to any vaccine, is unknown. Here we performed systems analyses of immune responses to the meningococcal polysaccharide and conjugate vaccines in healthy adults, in the broader context of our previous studies with the yellow fever and two influenza vaccines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
851
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 692 publications
(902 citation statements)
references
References 65 publications
29
851
1
4
Order By: Relevance
“…For example, since in the case of antibody responses, certain aspects of the sequelae of immunological events (e.g., innate sensing of vaccine by dendritic cells and other innate cells, T-cell expansion, B-cell expansion, generation of plasmablasts) that lead to antibody production may be conserved between different vaccines, it could be argued that there may be overlapping signatures of antibody responses to different vaccines, that are detectable in the blood. However, because different vaccines trigger distinct innate receptors [e.g., YF-17D activates the Toll-like receptors (TLR) 2, 3, 7, 8, 9, and the RNA helicases RIG-I and MDA-5 (22, 37); LAIV triggers TLR7 (38,39) and vaccines containing bacterial carbohydrates trigger TLR4 (27)], there may be expected to be different signatures of innate activation. To address this issue we performed a comparative systems analysis of signatures induced by different types of vaccines [YF-17D, TIV, the carbohydrate meningococcal vaccine (Menimmune), and the conjugate meningococcal vaccine (Menectra)] to see whether there are common predictors of antibody responses (27).…”
Section: Systems Vaccinology: Predicting Vaccine Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, since in the case of antibody responses, certain aspects of the sequelae of immunological events (e.g., innate sensing of vaccine by dendritic cells and other innate cells, T-cell expansion, B-cell expansion, generation of plasmablasts) that lead to antibody production may be conserved between different vaccines, it could be argued that there may be overlapping signatures of antibody responses to different vaccines, that are detectable in the blood. However, because different vaccines trigger distinct innate receptors [e.g., YF-17D activates the Toll-like receptors (TLR) 2, 3, 7, 8, 9, and the RNA helicases RIG-I and MDA-5 (22, 37); LAIV triggers TLR7 (38,39) and vaccines containing bacterial carbohydrates trigger TLR4 (27)], there may be expected to be different signatures of innate activation. To address this issue we performed a comparative systems analysis of signatures induced by different types of vaccines [YF-17D, TIV, the carbohydrate meningococcal vaccine (Menimmune), and the conjugate meningococcal vaccine (Menectra)] to see whether there are common predictors of antibody responses (27).…”
Section: Systems Vaccinology: Predicting Vaccine Efficacymentioning
confidence: 99%
“…Recent advances have used the tools of systems biology to probe the immune response to vaccination in humans (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Novel systems biology techniques allow integration of hierarchical levels of information, leading to a deconvolution of the complexity of biological systems (33).…”
Section: Systems Vaccinology: Predicting Vaccine Efficacymentioning
confidence: 99%
“…Indeed, following vaccination with Pandemrix during the 2009 H1N1 pandemic, some European countries, including Sweden and the UK, reported the emergence in a small number of cases of narcolepsy, an immune-mediated destruction of hypocretinsecreting neurons in the hypothalamus. Pandemrix elicits a transient, rapid and expansive activation of myeloid cells and effector cells, similar to the responses induced by other vaccines, including non-adjuvanted influenza vaccines [15][16][17][18][19][20]. However, it also differs from other vaccines; the Human Immune Response Dynamics (HIRD) study in our laboratory showed that Pandemrix provokes an overt early-lymphoid response within 24 h of vaccination, with prominent upregulation of IFN-γ transcription, which has not been observed in most other virus vaccine studies [16].…”
Section: Cellular Mechanisms For Gad-alum/influenza Vaccine Interferencementioning
confidence: 99%
“…A single dose should confer lifelong protective immunity [18], which is reflected by the vaccine's strong immune signature; notably, the efficient activation of antigen presenting cells, high neutralizing antibody titers, the induction of polyfunctional T cells, and long-term memory T and B cells [7]. A robust type I interferon response can be transiently observed in the blood transcriptomes of vaccinated individuals [19]. Owing to its strong elicitation of immune responses, the yellow fever vaccine has become a vector platform for vaccine development of heterologous viruses such as JEV and dengue.…”
Section: Yellow Fever Virusmentioning
confidence: 99%
“…Polysaccharide vaccines are lyophilized, heat-stable purified capsular polysaccharides from meningococci of defined serogroups (A, C, Y, and W-135), available as bi-, tri-, or tetravalent vaccines. However, these have been largely replaced by multivalent conjugate vaccines, in which polysaccharides from the above serogroups are conjugated to a carrier protein to induce a T cell-dependent immune response [19]. The conjugate vaccines are serogroup-specific and highly immunogenic, capable of eliciting humoral responses even in infants.…”
Section: Bacterial: Neisseria Meningitidesmentioning
confidence: 99%